Theoretical and experimental modelling the specific resistance of vertical ohmic contacts Au–Ti–Pd–n⁺-n-n⁺-Si in IMPATT diodes - Romanets, P.M.; Belyaev, A.E.; Sachenko, А.V.; Boltovets, N.S.; Basanets, V.V.; Konakova, R.V.; Slipokurov, V.S.; Khodin, А.А.; Pilipenko, V.А.; Shynkarenko, V.V.; Kudryk, Ya.Ya. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2016)
The method of electrophysical diagnostic of n⁺-n-n⁺ structures at the etching stage of manufacturing process of power IMPATT diodes has been proposed. A numerical method for specific contacts resistance calculation of vertical ohmic contacts with a non-uniform doping level has been developed. Vertical ohmic contacts Au–Ti–Pd–n⁺-n-n⁺-Si both before and after etching were used for experimental checking this model. It has been computed the value of contact resistance in the interface metal–n⁺ with correction of contribution of n⁺-n and n-n⁺ resistances to the total resistance. The values of total effective resistances of vertical ohmic contacts Au–Ti–Pd–n⁺-n-n⁺-Si may be calculated using the Cox–Strack method. We used solutions of Laplace’s equation for computation of specific contact resistance metal–n⁺ without contribution of interfaces n⁺-n and n-n⁺. The values of specific contact resistance were ~10⁻⁶ Ohm·cm². This method allows to control the manufacture process by monitoring the changes in electrophysical properties of the structure between etching cycles.